Performance analysis of single phase grid connected for PV inverter using PR controller with different filters - Nor Su’aida, Yusof (2018)
Since the PV producing a DC voltage, the grid-connected inverter is essential for matching the converted AC voltage with a purely AC grid voltage. The main drawback of the inverter is the harmonic distortion due to the switching during the conversion that is sensitive to the connected loads. Recently, the LCL filter is preferred compared to L filter and LC filter, for interfacing to the grid due to a good attenuate capacity of high order harmonics produced by grid-connected PV inverter. Nonetheless, the inherent resonance of the LCL filter is one of the challenging for stable operation of the system. To minimize the power losses, the damping can be applied to series with C only. Conventionally, the PI or PID controllers are the common current controller used in PV inverter due to its simplicities, but the lack of ability for AC voltage synchronization, steady-state errors and limited disturbance elimination capability. Lately, the advancement of proportional-resonance (PR) current controller to perform an efficient grid-connected PV inverter to replace the conventional PI current controller in regulating the quality of grid current and voltage has become interested in designing grid-connected PV inverter. However, due to an infinite gain of the PR controller leads to difficulty implementing in either analogue or digital controller. Therefore, a nonideal of PR controller is proposed in purpose to get promising performances of PV inverter. In this thesis, the single-phase grid-connected PV inverter system is designed and developed by applying a proposed non-ideal PR current controller with LCL filter active damping. Then, the performance of the proposed grid-connected PV inverter system is analysed, investigated and verified through simulation using MATLAB/Simulink under disturbances factors of voltage sag and frequency distortion. The total harmonic distortion (THD) is captured and compared with all filters using PI and non-ideal PR controllers. The frequency response of the grid-connected PV inverter with filters are analysed and compared using the Bode Diagram approach for robustness or stability analysis. The results show that the proposed controller has better performances during voltage sag and frequency distortion than the PI current controller. From THD analysis, it is absorbed that the LCL filter active damping has less harmonic in the output current compared with other filters. The current THD of LCL filter active damping with the proposed PR controller when voltage sag and frequency distortions are 0.43% and 0.46%, respectively. Lastly, in the stability analysis of frequency responses had shown that the proposed grid-connected PV inverter performed more stable than other filters and PI controller.